Addressing Complex Challenges in Coupled Natural and Human Systems Through Principled Pragmatism: A Case Study From Bangladesh - Smith, Kevin M.; Palash, Wahid; Choudhury, Enamul; Islam, Shafiqul (Frontiers in Water, 2021)
Some of the most persistent challenges facing society and the environment arise from an intricate coupling of natural and human systems (CNHS). These challenges resist traditional expert-driven problem-solving approaches and require a careful synthesis of both “explanation” and “understanding” to achieve equity and sustainability. Whereas explanations tend to be the domain of scientific experts who seek generalizable solutions through theory building, modeling, and testing, understandings represent the wisdom of practitioners that enables real-world problem solving to proceed by accounting for contextual values, capacities, and constraints. Using a case study from Bangladesh as an illustrative case of CNHS, we take an explanatory approach in using the extended case study method to show why and how an expert-led response to remediation of arsenic-contaminated wells led to unintended outcomes, which could have been accounted for if a complexity science informed framework of the problem was in place. The complexity frame keeps one alert to emergent patterns that otherwise remain unanticipated, and thereby, form the basis of adaptive actions. For a path forward in addressing complex CNHS problems, we introduce a novel problem-solving approach that combines pragmatic explanations and interpretive understandings with attention to emergent patterns. We argue that this problem-solving approach – which we term principled pragmatism – can effectively synthesize and apply scientific knowledge and local practical knowledge to develop and implement adaptive, actionable, and sustainable interventions.